Two new species of the genus Hoplopeza Bezzi (Diptera, Hybotidae, Ocydromiinae) from the high Andean forests of Colombia - Henao-Sepúlveda, Carolina; Barros, Luana Machado; Ale-Rocha, Rosaly; Wolff, Marta (Zootaxa, 2023)
Two new Andean species of Hoplopeza Bezzi are described and illustrated: Hoplopeza colombiana sp. nov. and Hoplopeza rafaeli sp. nov. These species are the first record from the Andean ecosystem of Colombia. In addition, the genus is diagnosed, the first description of the female terminalia, as well as a key and distribution map of the Andean species of the genus are presented.